Easy English step-by-step for ESL learners - Pelletier, Danielle (USA McGraw Hill Education, 2014)
The quickest route to learning a language is through a solid grounding in the basics. So what you won't find in 'Easy English Step-by-Step' is a lot of endless drills. Instead, this book features an original, step-by-step approach to learning English based on the way people naturally acquire language. With an emphasis on everyday language, this book gets you speaking and understanding English right away. From the beginning, you learn the most essential structures, which allows you to communicate in English almost immediately. Gradually, through a series of inter-connected "steps", you will progress in a logical way to more common concepts that govern how English is spoken and written. Along the way you will acquire hundreds of carefully selected vocabulary words that are most frequently used in everyday English.
Build a strong foundation in the basics of English! Pelletier links together important concepts by clear explanations, appropriate exercises, and helpful answers.
Includes index.
Keywords: English language; English language